Explorando o Uso de Competição eCooperação na Experiência deEstudantes de Computação deAcordo com seu Gamification UserType - Felipe Pereira Perez (2023)
Gamification has been used in recent years as an alternative to improve computing teaching. However, most studies focus on using classic gamification approaches (e.g., based on points, badges, and leaderboards) without considering individual aspects of students. Filling this gap, we explored (for four weeks) the use of a novelty gamification approach based on competition and cooperation (together) in the perception of undergraduate students according to their gamification user type. The results of the qualitative study (N = 15) based on thematic analysis show that i) the competition was more perceived by the students (regardless of their gamification user type), ii) students demonstrated more willingness to be in first place in the ranking (competition) and iii) it eas no perceived significant changes in the students’ perception over the three weeks. Our study contributes especially to the areas of Computing Education and Gamification, through insights related to the design of gamified classes based on competition and cooperation.